Determination of phagocyte activity in whole blood of carp (Cyprinus carpio) by luminol-enhanced chemiluminescence - Kubala, L; Lojek, A; Cíz, M; Vondrácek, J; Dusková, M; Slavíková, H (Veterinarni medicina, 1996)
In this study, the phagocytic capacity of fish peripheral blood leucocytes was studied using the luminol-enhanced chemiluminescence (CL) method. Suspensions of rice starch (1%) or opsonized zymosan particles-OZP (0.2%) were used as activators. The level of CL was detected at 25 degrees C in various whole blood volumes (100, 50, 20 a 10 microliters) during the mixed or unmixed measurement mode. The peak of CL in all starch-activated samples was between 2.0-4.0 mV, regardless of blood volume or a mode of measurement. Similar results were obtained for OZP activated CL when measured in the mixed mode. On the other hand, the peak of OZP activated CL in unmixed samples was much higher and it showed positive correlation with the increasing volume of blood in a sample. In contrast, no significant differences between the reaction curve areas were found for different blood volumes. After correction for phagocyte number the highest CL activity per cell was observed in the samples containing 10 microliters of blood. It can be concluded that 10-20 microliters of blood are optimal volumes for the measurements of respiratory burst activity in the whole blood of carp and opsonized zymosan particles should be used as an activator. At the same time, the unmixed mode of measurement seems to give better results than the mixed one.
Keywords: luminiscenční měření; Carps; Phagocytosis; fagocytóza; Luminescent Measurements; Animals; zvířata; Leukocytes; kapři; leukocyty